Om Fortuna - metafysikk i pedagogikken? - Æsøy, Knut Ove (Studier i Pædagogisk Filosofi, 2014)
This essay is an attempt to participate in a discussion about metaphysics today. I claim that metaphysic now seems silenced or taken for granted. Machiavelli’s idea of fortuna or fate (Norwegian: lagnad) represents question and perception that cannot be recognized empirically. My aim is to place Machiavelli into an ongoing discussion about the distinction between nature and culture and perception of reality (Norwegian: røyndom) as organic or harmonic. As part of this, I will discuss fortuna’s place in modern research based teacher education, which places our fate in the hand of science, the institutionalization of learning and the lack of virtue (Norwegian: dygd). In conclusion, I wish to express some critical remarks on this development, not taking into account the metaphysical speculation.